THE ADDITION OF ZEOLITE, ACTIVATED CARBON, CLOVE OIL, AND DIFFERENT SALINITY FOR GLUCOSE RESPONSE AND OSMOTIC PRESSURE ON JUVENILE GIANT PRAWN IN CLOSED TRANSPORT SIMULATION SYSTEM WITH HIGH DENSITY - . Humairani; Eddy Supriyono; Kukuh Nirmala (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
Long distance transportation of prawn juvenile usually use a closed system. Indonesian farmers often face problem in this juvenile transportation such as a low survival rate due to shrimp stress and changes in water quality during transportation. This study was aimed to determine the effect of salt, cloves oil, zeolite, and activated carbon for maintaining water quality in 24 hours juvenile giant prawn simulation transportation at high density. The study was conducted at laboratory scale with a complete randomized design with 4 treatments and 3 replicates. For each treatments, it was added 4.67 µl/L clove oil, 20 g of zeolite, 10 g of activated carbon within 4 (four) different salt concentration i.e., 0 g/L (A), 4.7 g/L (B), 9.4 g/L(C), 14.1 g/L(D) and K (without salt, clove oil, zeolites and activated carbon). The results showed that the addition of 9.4 g/L of salt, 4.67 µl/L clove oil, 20 g of zeolite, and 10 g of activated carbon produced the best results with the highest survival rate by 88±2% at the end of simulation transportation and 82±2.83% after rearing, water quality and physiological respons of shrimp remains in good condition at the simulation transportation and at rearing. Keywords: juvenile giant prawn, salt, high density, physiological responses